Phase Synchronization Control of Two Eccentric Rotors in the Vibration System with Asymmetric Structure Using Discrete-Time Sliding Mode Control - Xiaozhe Chen; Lingxuan Li (Shock and Vibration)
Control synchronization of two eccentric rotors (ERs) in the vibration system with the asymmetric structure is studied to make the vibration system obtain the maximum excited resultant force and the driven power. Because this vibration system is essentially an underactuated system, a decoupling strategy for the control goal of the same phase motion between two ERs is proposed to reduce the order of state equation of the vibration system. According to the master-slave control scheme, the complex control objects are converted into the velocity control of the master motor and the phase control of the slave motor. Considering the self-adjusting of the vibration system as interference, controllers of the velocity and the phase difference are designed by applying the discrete-time sliding mode control, which is proved by Lyapunov theory. A vibration machine is designed for evaluating the performance of the proposed controllers. Two control schemes are presented: controlling one motor and controlling two motors, and two group experiments are achieved to investigate the dynamic coupling characteristic of the vibration system in the state of control synchronization. The experimental results show that control synchronization is an effective and feasible technology to remove the limitation of vibration synchronization.